From prevalent to personal: how social exposure predicts attitudes toward non-suicidal self-injury and what prevalence reveals - James, Rosie; Lundgren, Elin; Daukantaité, Daiva; Nilsson, Magnus (Frontiers in Psychology, 2025)
IntroductionNon-suicidal self-injury (NSSI) is often met with stigma, which can deter individuals from seeking help. While most research on NSSI stigma has focused on clinical settings, the attitudes of those most likely to receive an NSSI disclosure, such as peers, friends, and family, remain underexplored. Building on qualitative findings that positive disclosure experiences can foster supportiveness, this study aimed to quantitatively examine how social exposure, gender, personal experience with NSSI, and mental health relate to supportive attitudes toward NSSI within social circles. We also assessed the prevalence and awareness of NSSI in close relationships, among university students.MethodA total of 1,430 Swedish university students completed a baseline survey, with 721 participating in a six-month follow-up. Measures included self-reported NSSI and mental health history, awareness of NSSI in others (social exposure), and attitudes toward NSSI.ResultsCorrelational and regression analyses showed all predictors were significantly associated with attitudes, with personal NSSI experience emerging as the strongest. Paired samples t-tests revealed a small but significant increase in supportive attitudes among participants who reported new social exposure at follow-up (n = 67), with no change observed among those without new exposure. Lifetime prevalence of NSSI in the sample was estimated at 38.7%, and 62.5% reported social exposure.DiscussionThese findings suggest that while personal experience with NSSI is the strongest predictor of supportive attitudes, increased social exposure may serve as an ethically modifiable factor in stigma reduction. Given the high prevalence and social visibility of NSSI in university populations, these settings may offer valuable opportunities for targeted anti-stigma initiatives.